Photoinitiated stereoselective direct C(sp²)–H perfluoroalkylation and difluoroacetylation of enamides - Zhao, Kai (2022)
A photoinitiated perfluoroalkylative coupling of enamides with perfluoroalkyl iodides and a visible-light-induced difluoroacetylation of enamides with ethyl bromodifluoroacetate have been developed, respectively. These transformations allow the efficacious and straightforward incorporation of biologically and physiologically privileged fluoro-containing moieties into synthetically eminent enamide scaffolds with excellent regio- and stereoselectivities under mild and environmentally friendly conditions.